Characteristics of traumatic brain injury in children and adolescents hospitalized in a Brazilian trauma reference center: a retrospective cross-sectional study - Melo, José Roberto Tude; Chaves, Caio Vinicius de Almeida; Kawano, Cindy; Fernandes, Maria Antonia Coladeti; Hussin, Reem; Oliveira, Jean Gonçalves de; Veiga, José Carlos Esteves (Arquivos de Neuro-Psiquiatria, 2025)
Background Approximately 20% of victims of traumatic brain injury (TBI) in Brazil are children and adolescents, with more than 900 deaths per year.Objective To describe the characteristics and epidemiological profile of children and adolescents with TBI in the city of São Paulo, Brazil, according to age groups and metropolitan area of occurrence of the events leading to trauma.Methods We conducted a retrospective cross-sectional study with a review of consecutive medical records of children and adolescents with TBI hospitalized and treated at a level-1 trauma center in São Paulo between 2019 and 2023.Results In the period proposed for the study, 196 children and adolescents suffered TBIs. They had a median age of 5 (interquartile range [IQR] 10–1.75) years and were predominantly boys (71%), of white skin color/race (55%), and coming from the north zone of the metropolitan region of São Paulo (44%). Domestic accidents were the main causes of TBI (61%), followed by traffic accidents (24%). The mean length of hospital stay was of 13 (standard deviation [SD] ± 26) days, and the in-hospital mortality rate was of 3%.Conclusion We found a predominance of children and adolescents with TBI coming from the north zone of the metropolitan region of São Paulo, with a prevalence of falls from heights above the ground among children ≤ 9 years of age and trampling among children older than this age. Preventive actions must be established after reflections on socioeconomic issues and considering the metropolitan area where the accidents occur and the age group.
Keywords: Craniocerebral Trauma; Glasgow Coma Scale; Brain Injuries; Wounds and Injuries